SISTEM INFORMASI MONITORING SALES DALAM MENJUAL PRODUK DENGAN FITUR SMS KODE VERIFIKASI BERBASIS WEB (STUDI KASUS TUNAS ARTA MANDIRI) - Julian Nur Pratomo; Dwi Sakethi; Didik Kurniawan (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
CV Tunas Arta Mandiri is a company that sells agricultural tools and fertilizers as well as being a distributor for small shops, in marketing the company has sales as the spearhead of the company, there are often problems in the marketing of products through sales such as lack of monitoring during seller transactions When this happens this triggers undisciplined for certain parties to deposit sales results in a timely manner, causing various losses for the company. In addition, the company also wants to improve good relations between the company and consumers by providing information related to the latest products and discounted prices. Based on these problems, Cv. Tunas Arta Mandiri needs a monitoring information system that can monitor buying and selling transactions directly and the system is also able to improve good relations between business actors and consumers. Therefore, a product sales monitoring information system was created that has 2 users, namely admin and sales, where sales are in charge of inputting transaction data directly and the admin is in charge of supervising transactions by confirming the data inputted by sales Programming is done with the PHP programming language, database MySQL, Apache2 web server, and Gammu as an SMS server. The hardware used to send SMS uses the Huawei E3278 modem and the method used in this study is waterfall. It is concluded that the monitoring information system has succeeded in monitoring the sale and purchase transactions directly by involving consumers and the system is also able to provide information via SMS to consumers about product information etc.